2019
DOI: 10.1021/acschembio.9b00024
|View full text |Cite
|
Sign up to set email alerts
|

An Oxidative Pathway for Microbial Utilization of Methylphosphonic Acid as a Phosphate Source

Abstract: Methylphosphonic acid is synthesized by marine bacteria and is a prominent component of dissolved organic phosphorus. Consequently, methylphosphonic acid also serves as a source of inorganic phosphate (Pi) for marine bacteria that are starved of this nutrient. Conversion of methylphosphonic acid into Pi is currently only known to occur through the carbon−phosphorus lyase pathway, yielding methane as a byproduct. In this work, we describe an oxidative pathway for the catabolism of methylphosphonic acid in Gimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…In this study, we found that Prochlorococcus strain MIT9301 can grow on MPn or HMPn as the sole source of P. Our data support the hypothesis that this capability is mediated by the putative phosphonate oxidative pathway encoded by the phnY and phnZ genes (1618). Strain MED4, a high-light-adapted strain isolated from the oligotrophic and P i -depleted surface waters of the Mediterranean Sea (22), lacks these genes and is accordingly unable to utilize 2-AEP (20).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In this study, we found that Prochlorococcus strain MIT9301 can grow on MPn or HMPn as the sole source of P. Our data support the hypothesis that this capability is mediated by the putative phosphonate oxidative pathway encoded by the phnY and phnZ genes (1618). Strain MED4, a high-light-adapted strain isolated from the oligotrophic and P i -depleted surface waters of the Mediterranean Sea (22), lacks these genes and is accordingly unable to utilize 2-AEP (20).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we present evidence that MIT9301 can utilize two previously unrecognized phosphonates enriched in marine HMW DOM, methylphosphonate (MPn) and hydroxymethylphosphonate (HMPn) (11). Our findings indicate that Prochlorococcus strain MIT9301 metabolizes these phosphonates to obtain P and can also excrete and assimilate the methyl group released during MPn and HMPn CP bond cleavage as formate, consistent with the MPn-specific oxidative mechanism identified in the marine planctomycete Gimesia maris (18). Our results support the hypothesis that phosphonates play an important role in the daily P nutrition of microbial communities in marine environments limited by P i and implicate the degradation of MPn and HMPn by Prochlorococcus as a potential source of formate for bacteria.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations